Knowledge, Attitude and Practices Regarding COVID-19 among Undergraduate Students of A Medical College in District Anantnag, Kashmir - Mohsina Mukhtar; Mahbooba Rasool; Shahnaz Nabi; Muneer Ahmad Masoodi; Suhail Nazir (Masters Program in Public Health, 2022)
Background: The control measures implemented against COVID-19 infection are affected largely in turn by the knowledge, attitudes, and practices (KAP) towards COVID-19. The medical undergraduates being most active users of social media could have a huge impact over spread as well as control of this pandemic. So in order to evaluate their understanding of COVID-19. This study was aimed to assess knowledge, attitude and practices associated with COVID-19 among the undergraduate medical students.Subjects dan Method: A cross sectional study using an online survey was conducted among the medical students of Government Medical College, District Anantnag, J&K. All the medical students enrolled in this medical college were included in the study. Universal sampling was followed and a total of 183 medical students were included in the study. Data was collected by using a pre-tested semi-structured questionnaire through online survey form. The dependent variables were Knowledge, Attitude and Practice regarding COVID-19. The independent variables were demographic characteristics like age, gender, residence etc. Frequencies were obtained using descriptive statistics using appropriate statistical tool for analysis.Results: A total of 183 medical students participated in this study. All the subjects knew about corona virus and their main source of information was social media (n=131; 71.4%). About 95.6% knew about mode of transmission, and 91.2% knew about all major symptoms of corona virus infection. Most of the participants felt that COIVD-19 is a serious (n=137; 74.9%) disease and that lockdown is helping in reducing the number of cases (n=157; 85.8%). Our study also showed that 86.9% wash their hands regularly, 90.2% wear a face mask to avoid transmission, and 89.1% followed the lockdown guidelines.Conclusion: The present study showed that these medical students seem to have satisfactory knowledge, positive attitude and good practices regarding COVID-19. Keywords: COVID-19, knowledge, attitude, practice, medical students, Anantnag Correspondence:Suhail Nazir. Department of Surgery, Government Medical College, Srinagar, Jammu and Kashmir. India. Email: suhailbhat669@gmail.com.